ANALYSIS OF FACTORS ASSOCIATED WITH SLEEP QUALITY IN PREGNANT WOMEN IN THE THIRD TRIMESTER: A CROSS-SECTIONAL STUDY - Wachyu Amelia; Iis Sukmawati (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
The pregnancy process requires special care because it relates to the health of the mother and fetus. Various complaints and discomforts often arise during pregnancy, which can interfere with the activities of pregnant women. The purpose of this study was to identify factors related to the quality of sleep in pregnant women in their third trimester. This study was an analytical survey using a cross-sectional approach conducted at TPMB ZIANDTA in Ogan Komering Ulu Regency from July to December 2025. The population of this study consisted of 60 pregnant women in their third trimester. The sampling technique used was non-random sampling with a purposive sampling method, resulting in 35 respondents. From the Chi-Square test results, ρ Value of 0.007 (< 0.05) was obtained, meaning that there is a relationship between the mother's age and the sleep quality of pregnant women in their third trimester. ρ Value of 0.011 (< 0.05) was obtained, meaning that there is a relationship between prenatal exercise and the sleep quality of pregnant women in their third trimester.  ρ Value of 0.003 (< 0.05) was obtained indicating a relationship between anemia and sleep quality in pregnant women in their third trimester, and ρ value of 0.011 (< 0.05) indicating a relationship between BMI and sleep quality in pregnant women in their third trimester. It is recommended that health workers improve the health status of mothers so that the sleep quality of pregnant women is more adequate.